Hygiene Sanitation and Identification of Escherichia coli in Fresh Goat Milk - Lidya Novita; Sri Mulyani; Yola Humaroh (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Riau, 2022)
Fresh milk is the result of the milking process and has not received any treatment except cooling. Its high nutritional value causes milk to become a very suitable medium for microorganisms growth and development so that in a very short time milk becomes unfit for consumption. One example of this bacterium is Escherichia coli (E. coli). This study aims to determine the description of hygiene and sanitation and the identification of Escherichia coli. This study is survey research and qualitative descriptive. The sampling method of fresh goat's milk is using the total sampling method. The samples in this study were 2 fresh goat's milk at the farms of Umban Sari Rumbai and Sidomulyo barat Pekanbaru city. The results of this study indicate that the hygiene and sanitation of farm A (Umban Sari) are in agood category, while farm B (Sidomulyo barat) only has good sanitation of cages and equipment. The results of the identification of E. coli from the two farms showed that there was no contamination of E. coli bacteria in fresh goat's milk. It was found that farm hygiene did not meet the hygiene requirements and obtained laboratory results that Escherichia coli bacteria were not found in fresh goat's milk. Further analysis can be conducted to the other kind of coliform bacteria.